Restorasi Indirect Mahkota Jaket PFM dengan Pasak Fiber Pasca Perawatan Saluran Akar Tunggal: Laporan Kasus - Inneke Cahyani; Ferina Ayu Maharani Haibar (Journal of Educational Innovation and Public Health, 2026)
Secondary caries is a primary cause of restoration failure; if left untreated, it can progress to pulp necrosis and periapical lesions. For anterior teeth, treatment success depends not only on eliminating infection but also on restoring function and aesthetics through appropriate post-endodontic restoration. A patient presented with discoloration and structural damage to a previously restored maxillary lateral incisor. Clinical and radiographic examinations revealed secondary caries leading to pulp necrosis and a periapical lesion. Treatment involved root canal therapy using the step-back technique, irrigation with 2.5% sodium hypochlorite (NaOCl), and intracanal medication with calcium hydroxide. Once the root canal was asymptomatic, obturation was performed using the lateral condensation technique with gutta-percha and sealer. Post-endodontic restoration was achieved using a fiber post, core build-up, and a porcelain-fused-to-metal (PFM) crown. NaOCl and calcium hydroxide play a role in eliminating microorganisms and promoting periapical tissue healing. Fiber posts provide superior stress distribution, while PFM crowns effectively restore the strength and aesthetics of anterior teeth. The combination of root canal therapy, a fiber post, and a PFM crown successfully restored the tooth's function, aesthetics, and structural integrity, resulting in a favorable prognosis.